2019
DOI: 10.1038/s41598-019-42888-2
|View full text |Cite
|
Sign up to set email alerts
|

Positive verbal suggestion optimizes postural control

Abstract: Balance is a very important function that allows maintaining a stable stance needed for many daily life activities and for preventing falls. We investigated whether balance control could be improved by a placebo procedure consisting of verbal suggestion. Thirty healthy volunteers were randomized in two groups (placebo and control) and asked to perform a single-leg stance task in which they had to stand as steadily as possible on the dominant leg. The task was repeated in three sessions (T0, T1, T2). At T1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 76 publications
(83 reference statements)
1
19
0
Order By: Relevance
“…Reduced COP movements during quiet standing have previously been described in healthy young adults following a placebo procedure (Villa-Sánchez et al, 2019). In agreement with our hypothesis and previous literature, our findings confirm that participants in the placebo group exhibited a reduced range (greater precision achieved by the postural control system) of the COP and concomitantly increased perceived stability after expectation manipulation.…”
Section: Reduced Postural Sway Following a Placebo Proceduressupporting
confidence: 93%
See 3 more Smart Citations
“…Reduced COP movements during quiet standing have previously been described in healthy young adults following a placebo procedure (Villa-Sánchez et al, 2019). In agreement with our hypothesis and previous literature, our findings confirm that participants in the placebo group exhibited a reduced range (greater precision achieved by the postural control system) of the COP and concomitantly increased perceived stability after expectation manipulation.…”
Section: Reduced Postural Sway Following a Placebo Proceduressupporting
confidence: 93%
“…Additionally, our placebo procedure may have enhanced positive affect and resulted in increased effort. However, in a previous study, positive verbal suggestions elicited a reduction in postural sway without any changes in balance effort (measured using the Borg 0-10 scale; Borg, 1982;Villa-Sánchez et al, 2019). Therefore, the relative contribution of increased effort and motivation on postural stability following a placebo procedure remain unclear.…”
Section: Reduced Postural Sway Following a Placebo Proceduresmentioning
confidence: 95%
See 2 more Smart Citations
“…Emergent studies have suggested a mechanical and neurophysiological mechanism (peripheral, spinal and supraspinal) as the base of the effects induced by the therapeutic interventions adopted by the physiotherapists [35][36][37]. Considering the supraspinal mechanisms, placebo and nocebo effects were indicated as important top-down modulators of patient's symptoms, mainly pain and motor performance [38][39][40][41][42][43][44], thus becoming elements that physiotherapists should attentively consider in their clinical practice [17].…”
Section: Introductionmentioning
confidence: 99%